THE EFFECT OF SPECIAL EXERCISES ACCORDING TO SOME BIOMECHANICAL VARIABLES OF THE ENERGY TRANSFER INDEX TO DEVELOP THE FOOTBALL SCORING SKILL OF YOUTH PEOPLE - M.DR.THaer Awad Jabar Al-Bidany (Proximus Journal Publishing, 2024)
The research included five chapters, where the first chapter contained the introduction and the importance of the research, as its importance was summarized in developing the scoring skill of youth football players by preparing special exercises according to some biomechanical variables of the energy transfer index that the player must apply while performing basic football skills. The research problem is through the researcher’s experience, and through his follow-up of youth teams; He noticed that there is a weakness in the basic skills, especially the scoring skill, and the researcher attributes this to several reasons, one of which is the lack of use of diversity in applications and training methods. Accordingly, this study came as an attempt to develop special exercises in some biomechanical variables and reveal their effect on the energy transfer index for the scoring skill. Because of the importance of the energy transfer index in achieving the best possible performance and thus achieving the desired and ideal achievement due to its importance in winning the match, the most important goals of the research are to prepare special physical exercises on some biomechanical variables for the energy transfer index for scoring skill in youth soccer, as well as identifying the effect of special physical exercises on some variables
Keywords: Resistance exercises; Bio Kinematic; Power transfer indicator